THE NEEDS AND ATTITUDES OF PEOPLE TO THE MEDIA IN THE DISSEMINATION OF INFORMATION BY GLOBAL HEALTH ORGANIZATIONS - G. Kurbanova (Zeta Repository, 2023)
Actively developing various sources of information have become the main consumer market for mankind and have brought to life a special kind of media - the consumer media market, the content of which indicates the emergence of previously unknown elements in interaction with the audience. All stages of the development of human society were carried out on a technical basis. Automation has led to increased productivity.